Gang Risk Factors and Academic Readiness in a Southern Middle School - Hilgert, Larry (2014)
The current Georgia study examines middle-school-aged gang and non-gang members regarding the risk factors of gang membership and potential effects of these risk factors on academic achievement. Participants, 406 eighth grade students from a suburban middle-school, completed a 42-item survey assessing an array of demographic and risk factor variables. In addition, students provided self-report information regarding their success on national standardized testing used to measure academics readiness. Of the 28 variables analyzed, lower academic readiness was associated with ethnicity and/or gang membership. Findings are discussed in light of the complexity of the gang issue and the importance of recognizing the specificity associated with demographic predictors. Researchers are encouraged to continue exploring gang involvement in a variety of settings investigating differences in locality, school structure, and race/ethnicity. Teachers, parents, school administrators, and other key stakeholders may examine the aforementioned differences to collaboratively develop and share prevention and intervention successes and failures to enhance academic readiness and reduce gang involvement among youth